2017
DOI: 10.1016/j.pbiomolbio.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Load-dependent effects of apelin on murine cardiomyocytes

Abstract: The apelin peptide is described as one of the most potent inotropic agents, produced endogenously in a wide range of cells, including cardiomyocytes. Despite positive effects on cardiac contractility in multicellular preparations, as well as indications of cardio-protective actions in several diseases, its effects and mechanisms of action at the cellular level are incompletely understood.Here, we report apelin effects on dynamic mechanical characteristics of single ventricular cardiomyocytes, isolated from mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
(77 reference statements)
1
20
0
Order By: Relevance
“…Apelin receptor signalling is known to increase cardiac contractility and output (Brame et al, 2015;Maguire et al, 2009;Szokodi et al, 2002), possibly by activating myosin light chain kinase to increase myofilament calcium sensitivity (Perjés et al, 2014) and by a positive lusitropic effect (Peyronnet et al, 2017), so the enhanced cardiac performance does not require an increase in oxygen consumption (Charo et al, 2009). Apelin receptor signalling is known to increase cardiac contractility and output (Brame et al, 2015;Maguire et al, 2009;Szokodi et al, 2002), possibly by activating myosin light chain kinase to increase myofilament calcium sensitivity (Perjés et al, 2014) and by a positive lusitropic effect (Peyronnet et al, 2017), so the enhanced cardiac performance does not require an increase in oxygen consumption (Charo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apelin receptor signalling is known to increase cardiac contractility and output (Brame et al, 2015;Maguire et al, 2009;Szokodi et al, 2002), possibly by activating myosin light chain kinase to increase myofilament calcium sensitivity (Perjés et al, 2014) and by a positive lusitropic effect (Peyronnet et al, 2017), so the enhanced cardiac performance does not require an increase in oxygen consumption (Charo et al, 2009). Apelin receptor signalling is known to increase cardiac contractility and output (Brame et al, 2015;Maguire et al, 2009;Szokodi et al, 2002), possibly by activating myosin light chain kinase to increase myofilament calcium sensitivity (Perjés et al, 2014) and by a positive lusitropic effect (Peyronnet et al, 2017), so the enhanced cardiac performance does not require an increase in oxygen consumption (Charo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proposed possible explanations for the observed benefits of MM07. Apelin receptor signalling is known to increase cardiac contractility and output (Brame et al, 2015;Maguire et al, 2009;Szokodi et al, 2002), possibly by activating myosin light chain kinase to increase myofilament calcium sensitivity (Perjés et al, 2014) and by a positive lusitropic effect (Peyronnet et al, 2017), so the enhanced cardiac performance does not require an increase in oxygen consumption (Charo et al, 2009). MM07-induced haemodynamic improvement was confirmed by invasive right heart catheterisation.…”
Section: Discussionmentioning
confidence: 99%
“…It may relate to methodological differences or differences in data handling. Our experiments involved the stretch of ventricular myocytes using 10 µm diameter compliant carbon fibers, which stick to the cells through biophysical interactions (Peyronnet et al, 2017). The previous work from Prosser et al (2011) used 20 µm stiff glass rods adhered to the cells with a biological adhesive (Myotak, composed of laminin, entactin, heparin sulfate proteoglycan, gentamicin, Dulbecco's Modified Eagle Medium, collagen IV, Alexa Fluor-647 conjugated to bovine serum albumin, and an inert alumina silica aggregate with a diameter of 1 µm, dissolved in 100 µM BSA).…”
Section: Comparison Of Results To Previous Studiesmentioning
confidence: 99%
“…Cells were placed on coverslips coated with poly-2-hydroxyethyl methacrylate (poly-HEMA; Sigma-Aldrich, Tokyo, Japan) to prevent cellular adhesion. Carbon fibers (10 µm in diameter) mounted in glass capillaries that adhere to isolated cells through biophysical interactions (Peyronnet et al, 2017) were attached to either end of an individual cell. For experiments examining the effect of stretch on Ca 2+ sparks, one "compliant" (1.2 mm) and one "stiff " (0.6 mm) carbon fiber were used, while for the ROS experiments two compliant (1.2 mm) carbon fibers were used (Tsukuba Material Information Laboratory, Tsukuba, Japan).…”
Section: Single Cell Stretchmentioning
confidence: 99%
“…To this end, cardiomyocytes were imaged with a MyoCam-S camera (IonOptix) on an inverted microscope (DM IRBE, Leica Microsystems). Sarcomere length was calculated in real time by a Fast Fourier Transform of the power spectrum of the striation pattern (IonWizard, IonOptix) 61 . Cells were field stimulated at 14 V/0.25 Hz with a Myopacer (IonOptix).…”
Section: Methodsmentioning
confidence: 99%